Identification of Multiple Grain Shape-Related Loci in Rice Using Bulked Segregant Analysis With High-Throughput Sequencing - Wu, Lian (Front Plant Sci, 2020)
Grain shape (GS) is an important agronomic trait that can improve rice breeding for optimal appearance quality, and it varies highly between indica and japonica subspecies. In this study, we conducted a genome sequencing of a series of recombination inbred lines (RILs) derived from a cross between japonica variety Shennong265 (SN265) and indica variety R99, and we successfully detected seven loci associated with GS. Subsequent analysis showed that a major quantitative trait locus (QTL) corresponded to the qSW5/GW5. To identify a main-effect locus, we conducted bulked segregant analysis (BSA) in two F(2) populations. A 0.8-Mb region on chromosome 9 was identified as the candidate region of GS. There are 101 predicted genes in this region, and eight single nucleotide polymorphisms/insertions and deletions (SNPs/INDELs) caused frameshift. We found that a 637-bp stretch in exon 5 of the DENSE AND ERECT PANICLE 1 (DEP1) locus in SN265 was replaced by a 12-bp sequence. The two types of CRISPR/Cas9 gene-edited plants confirmed that DEP1 affected GS, and both Gγ and Cys-rich domains participated in this regulatory mechanism. These findings improve our understanding of the underlying mechanism of GS in rice and provide an effective and rapid strategy for the identification of main-effect loci of target traits.